THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL ATTITUDE ON FINANCIAL MANAGEMENT OF CHICKEN FARMING MSMES IN TANETE VILLAGE, MARITENGNGAE DISTRICT, SIDENRENG RAPPANG REGENCY - Fauziah, Rafiah; Salida, Amrizal; Basri, Jumriah; Haeril, Haeril (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to determine the influence of financial literacy and financial attitude on the financial management of Chicken farming MSMEs in Tanete Village, Maritengngae District, Sidenreng Rappang Regency. The method used in this research is a quantitative approach with an associative design. Data was collected through questionnaires distributed to 57 respondents. The data obtained were then tested for validity, reliability, and normality. Before conducting path analysis and hypothesis testing, the data were converted using the Method of Successive Interval (MSI). The analytical technique used was path analysis, and the data were processed with the help of SPSS software. The results showed that, partially, financial literacy has a positive and significant effect on financial management, as does financial attitude, which also has a positive and significant effect. Simultaneously, both variables significantly influence the financial management of MSMEs. These findings indicate that improving financial literacy and financial attitudes can support more effective business financial management.